Development of Learning Media for E-Booklet Human Reproductive System Materials to Improve Cognitive Learning Outcomes of High School Students - Ade Nur Eliana; Oding Sunardi; Lufty Hari Susanto (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2022)
This study aims to develop a learning media E-Booklet for reproductive system materials to improve students' cognitive learning outcomes in biology subjects for the human reproductive system. This research was conducted from December 2020 to June 2021. The trial in this study consisted of one class using the model one group pretest- posttest design. The results of the validation related to the feasibility of the media E-Booklet obtained a score of 91% in the Very Valid category. The results of the pretest and posttest scores of class XI IPA-1 students in improving students' cognitive learning outcomes. This is indicated by the average value of the pretest before using the learning media, which is 33. While the average posttest after using the learning media is 87 with a Biology minimum completeness criteria value of 72. The N-Gain value has an average of 0.81 or in N Gain% is 81% indicating high category. This shows that the learning media E-Booklet material for the human reproductive system can improve students' cognitive learning outcomes.